A Continent Divided? Diverging EU Actors´ Perspectives on CSDP and CFSP Reforms - Zdeněk Rod; Michael Jarkovský (Obrana a Strategie)
This study examines the divergent positions of key European Union actors - Member States, the European Commission, the European Parliament, and the High Representative/Vice-President - across four critical debates on the reform of the Common Foreign and Security Policy (CFSP) and the Common Security and Defence Policy (CSDP). These debates include the proposed introduction of Qualified Majority Voting in CFSP decision-making; the establishment of an EU Rapid Deployment Capacity; the use of ‘coalitions of the willing’ under Article 44 of the Treaty on European Union; and operationalising the Union’s mutual assistance clause under Article 42(7) TEU. Through a combined textual and contextual analysis of academic literature, official documents, and public statements by EU actors, the study maps the evolving landscape of support and resistance to these initiatives. The findings reveal dynamic shifts in Member State positions amid changing geopolitical and security contexts. Understanding these nuances is essential for policymakers shaping the future trajectory of the EU’s foreign, security, and defence policies.